Bangladesh Midlife Women's Health Study (BMWHS): Methods, challenges and experiences. Issue 1 (January 2015) - Islam, Rakibul M.; Bell, Robin J.; Hossain, Mohammad B.; Davis, Susan R.
Highlights Cultural and religious sensitivities and safety were addressed by engaging community leaders. Age at menarche in relation to marriage and child birth enabled age estimation as life events were inadequate. Identification of challenges for other researchers planning to conduct survey about women's health issues in similar contexts.